2022
DOI: 10.15441/ceem.22.399
|View full text |Cite
|
Sign up to set email alerts
|

Intra-arrest transesophageal echocardiography during cardiopulmonary resuscitation

Abstract: Determining the cause of cardiac arrest (CA) and the heart status during CA is crucial for its treatment.Transesophageal echocardiography (TEE) is an imaging method that facilitates close observation of the heart without interfering with cardiopulmonary resuscitation (CPR). Intra-arrest TEE is a point-of-care ultrasound technique that is used during CPR. Intra-arrest TEE is performed to diagnose the cause of CA, determine the presence of cardiac contraction, evaluate the quality of CPR, assist with catheter in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…Kim et al reported that TEE could be useful for evaluating the LMT pathology in cases of severe intraoperative hypotension caused by acute occlusion of the left main coronary ostium by mobile vegetation 4. Compared with transthoracic echocardiogram, TEE provides excellent echocardiographic windows to the heart regardless of the patient’s body type5; furthermore, it has a high accuracy and can provide further details regarding thrombus and vegetation 6…”
Section: Descriptionmentioning
confidence: 99%
“…Kim et al reported that TEE could be useful for evaluating the LMT pathology in cases of severe intraoperative hypotension caused by acute occlusion of the left main coronary ostium by mobile vegetation 4. Compared with transthoracic echocardiogram, TEE provides excellent echocardiographic windows to the heart regardless of the patient’s body type5; furthermore, it has a high accuracy and can provide further details regarding thrombus and vegetation 6…”
Section: Descriptionmentioning
confidence: 99%